Latihan fisik pada anak penderita asma: Studi literatur - Siti Rahmawati; Iwan Shalahuddin; Gusgus Ghraha Ramdhanie (Holistik Jurnal Kesehatan, 2021)
Children with asthma and physical exercise: A literature StudyBackground: Physical exercise in children with asthma is very important, but the negative perception that there will be a recurrence of asthma attacks after physical exercise makes them reluctant to do physical exercise. This has a negative impact on fitness which will cause the rate of recurrence of asthma to increase so there will be an increase in the number of emergency management and hospitalizations, followed by poorly attended rates in school, and decreased productivity.Purpose: To synthesize existing research on various physical exercises in children with asthma.Method: This literature design uses a narrative review method. Search for articles specified in Indonesian, namely "Latihan Fisik" AND "Anak" AND "Asma". And for the English article, namely "Physical Exercise" AND "Children" AND "Asthma".Results: Finding 10 articles that were identified and relevant to the purpose of the study. The result of the literature study illustrated that there were several physical exercises that were applied by children with asthma as non-pharmacological therapy, including physical exercise swimming, active play, cycling/static cycling, HIIT aerobic physical exercise, treadmill, and indoor physical exercise (low intensity: walking, flexibility, coordination/relaxation High intensity: running, weight training with companion/sports team).Conclusion: All articles showed that physical exercise could maintain body fitness, could improve asthma control, and could improve the quality of life of children with asthma. This literature study is to be used as an information and educational content in nursing interventions on asthma management in children.Keywords: Asthma; Children; Physical exercisePendahuluan: Latihan fisik pada anak penderita asma sangat penting, namun adanya persepsi negatif akan adanya kekambuhan serangan asma setelah latihan fisik membuat enggan melakukan latihan fisik. Hal tersebut berdampak negatif pada kebugaran tubuh yang akan menyebabkan angka kekambuhan asma meningkat sehingga akan terjadi peningkatan angka penanganan gawat darurat dan rawat inap, angka absensi anak disekolah meningkat dan menurunkan produktivitas.Tujuan: Untuk mensintesis penelitian yang telah ada mengenai berbagai latihan fisik pada anak penderita asma. Metode:  Desain literatur ini menggunakan metode narrative review. Pencarian artikel  yang ditentukan dalam Bahasa Indonesia yaitu “Latihan Fisik” DAN “Anak” DAN “Asma”. Dan untuk artikel Bahasa Inggris yaitu “Physical Exercise” AND “Children” AND “Asthma”.Hasil: Didapatkan 10 artikel yang teridentifikasi dan relevan dengan tujuan penelitian. Hasil studi literatur menggambarkan terdapat beberapa latihan fisik yang bisa dilakukan oleh anak penderita asma sebagai terapi nonfarmakologis, diantaranya ada latihan fisik berenang, bermain aktif, bersepeda/bersepeda statis, latihan fisik aerobic HIIT, treadmill dan latihan fisik didalam ruangan (intensitas rendah: berjalan, fleksibilitas, koordinasi/relaksasi. Intensitas tinggi : berlari, latihan beban dengan pendamping/olahraga tim).Simpulan: Dari semua artikel menunjukkan bahwa dengan latihan fisik dapat menjaga kebugaran tubuh, dapat meningkatkan kontrol asma serta dapat meningkatkan kualitas hidup anak penderita asma. Studi literatur ini diharapkan dapat dijadikan informasi dan muatan edukasi dalam intervensi keperawatan pada manajemen asma pada anak.